Identificação de paleocanais na região da confluência entre os rios Ivaí e Paraná com o uso de dados de sensoriamento remoto e reconhecimento de fácies sedimentares - De Morais, Eduardo Souza [UNESP]; Dos Santos, Manoel Luís; Stevaux, José Cândido (My University, 2012)
The confluence of Ivaí River together with the Paraná one is located near Icaraíma city on the Northwest of Paraná State. In this region, several paleochannels showed quaternary dynamic of Ivaí and Paraná Rivers floodplain. The aim of study was to apply multispectral indices and a data transformation of Landsat 5 TM data, associated with fieldwork and sedimentary facies to identify paleochannels. The results of the Normalized Difference Vegetation, Normalized Difference Water e Modificated Normalized Difference Water indices did not show satisfactory gains. However, the Tasseled Cap Wetness has provided an important gain of information on recognizing paleochannels facies. Through the remote sensing results sediment cores were realized and the sedimentary facies showed its correspondence with remote sensing interpretation.
The confluence of Ivaí and Paraná Rivers is located near Icaraíma town on Northwest of Paraná State
Keywords: Indices; Ivaí river; Paleochannels; Remote sensing; Sedimentary facies